Job Satisfaction of Agricultural Graduates Engaged in Selected Avenues of Employment in Alleppey District - Kalavathi S (Department of Agricultural Extension, College of Agriculture, 1989)
The study was conducted in Alleppey District with a sample of 110 Agricultural graduates working in three avenues of employment viz., Department of Agriculture (60 respondents), Banks (30 respondents) and Agricultural University (30 respondents). The data were collected through interviews with the respondents. The data were analysed by applying percentage analysis, simple correlation, path analysis, Chi-square test, kruskal-wallis test and Friedman’s test. The results indicated that the agricultural graduates working in banks felt higher satisfaction on their job, followed by the agricultural graduates in the University and Department of Agriculture respectively in their order of satisfaction. Their personal factors (age, sex and the like) contributed very little to job satisfaction, whereas the job- related factors (Job Motivation, Job attitude and the like) were having significant contribution to job satisfaction. Job motivation expressed maximum direct as well as indirect effects within the three avenues of employment. Most negatively contributing factor was job esteem. Half of the agricultural graduates working in the three avenues of employment viz., Department of Agriculture, Banks and Kerala Agricultural University both perceived and performed their duties on the job at a higher order. The personal in the Banks and Agricultural University evidenced significant difference in the levels of their perception and performance in the areas of their job, namely, planning, Execution, Financing. Administration and supervision, Monitoring and Evaluation and Technical duties. Planning with Monitoring and Evaluation was considered most by the banking personnel. The Agricultural University personnel evidenced significant importance in Planning, Execution and supervisory process within their job. Departmental personnel perceived and performed all the areas of job duties on par. The results also indicated a positive relationship between job perception, job performance and job satisfaction amongst the agricultural graduates in all the three avenues of employment.